The Role Of Strategic Management Accounting On Digital Payment - Laora Safira; Galuh Pratiwi; Yanuar Ramadhan (UNIVED Press, 2025)
The advancement of digital technology has transformed how people conduct financial transactions, shifting from cash-based to faster, more convenient digital payments. However, this shift also introduces new risks, including increased threats of financial crimes such as money laundering and terrorism financing. This study aims to explore the role of strategic management accounting in supporting digital payment systems, particularly in improving operational efficiency and transaction security. The research employs a qualitative descriptive approach based on secondary data from literature studies. Findings indicate that strategic management accounting plays a vital role in automating transaction processes, managing digital service costs, and detecting suspicious activities early. The integration of accounting information systems enables organizations to enhance efficiency and strengthen financial monitoring through real-time data. Therefore, strategic management accounting is a key component in maintaining the integrity of digital financial systems amid growing cybercrime threats.